Dünya’ da ve Türkiye’ de yaşanılan krizler: finansal serbestleşme hareketleri - İnce, İsmail (My University, 2000)
CRISES ENCOUNTERED IN THE WORLD AND IN TURKEY: FINANCIAL LIBERALIZATION MOVEMENTS (SUMMARY) During the period starting from the 1980s towards present, Turkey went through financial liberalization and consequent economic crises. From the viewpoint of developing countries like Turkey, the economic policies and policies determined by the governments made financial liberalization necessary for achieving the level of developed countries. The financial liberalization in the Turkish economy started from the year 1980. With financial developments such as unconstrained interest rates and determination of exchange rates in the market conditions, and liberalization of international capital movements in 1989; it occurred in two stages: In the domestic market and in the foreign market. We can say that it developed in Turkey in harmony first with domestic financial liberalization and then with the liberalization of international capital movements. Thus, in the process of such developments encountered, Turkey, being a developing country, was sometimes negatively affected by both domestic economic policies and developments in the World during this liberalization process, encountering economic crises in some periods. These crises negatively affected the development level of the country, and prevented its being in an effective position in the international markets. The aim of this study is to investigate Turkey's financial liberalization and consequent economic development after 1980 because of the aforementioned developments and reasons, and furnish the necessary economic measures to be applied against the economic crises encountered. In this context, these developments were studied in 3 main sections. In the first section, the definition of financial liberalization and policies providing its development were explained in a theoretical basis, and the operation of free market economy in international markets was touched on. In the second section; the financial situation and development of Turkey after 1980 were handled according to periods, and the economic crises arising from the financial liberalization as a consequence of the developments were explained. In the third section, the crises encountered in the World (Asian Crisis, Russian Crisis, and Global Crisis), and in the fourth section the effects of these crises on the Turkish and World economies were studied and solutions were suggested. During the period starting from the 1980s towards present, Turkey went through financial liberalization and consequent economic crises. From the viewpoint of developing countries like Turkey, the economic policies and policies determined by the governments made financial liberalization necessary for achieving the level of developed countries. The financial liberalization in the Turkish economy started from the year 1980. With financial developments such as unconstrained interest rates and determination of exchange rates in the market conditions, and liberalization of international capital movements in 1989, it occurred in two stages, in the domestic market and in the foreign market. We can say that it developed in Turkey in harmony first with domestic financial liberalization and then with the liberalization of international capital movements. Thus, in the process of such developments encountered, Turkey, being a developing country, was sometimes negatively affected by both domestic economic policies and developments in the World during this liberalization process, encountering economic crises in some periods. These crises negatively affected the development level of the country, and prevented its being in an effective position in the international markets. The last quarter century witnesses important changes regarding the national economies. With regard to financial markets, the change started with the collapse of Bretton Woods system at the beginning of 1970s and transition of international markets from a regular period to an irregular period; and this period was scene to liberalization and deregulation movements. The financial markets went through a continuous change from the beginning of 1970s. The presence of economic instabilities and uncertainties, formation of new financial products, and developments occurring in the technological field (especially in the field of communication) together with liberalization, were effective in the formation of the main causes of these developments. The most important purpose of liberalization and deregulation movements are on the points of limiting the public controls on the markets, and making the resource distribution more effective by increased effectiveness of market mechanism. This approach is also the endeavor to strengthen the financial structures of the financial institutions and to make them survive as more stable market participators in the new competitive system, and to provide them not to pose any risk for the markets. With regard to financial markets, these works, which were carried on, are in harmony with trade liberalization and privatization policies, which are more macro policies. The new period, in principle, became a period in which the government withdrew from its economic activities, became smaller, and concentrated on functions such as defense, justice, health, education, and environment. Parallel to these chances, the restrictions on international fund movements in financial markets were lifted, the restrictions on interest and exchange rates were abandoned, inflows and outflows to and from the markets were made more free, and the borders between the subdivisions of financial markets loosened, and even disappeared in many countries, thus enabling the financial institutions to operate in a wider range. As a result of these developments, the capital costs decreased because of increased competency, and international capital costs and yields became very close to each other. The continued domination of capitalism in the years of rivalry between the two important economic systems in the international field decreased the influence of public authorities, making transactions possible under free market mechanism. As a result of liberalization movements and developments in technology and telecommunication, capital-fund movements between financial markets intensified, and markets which previously operated independently from each other, with the increasing rivalry, started to show activity as if they were virtually a single market. Turkey's liberalizing financial policies from 1980 to present are important with regard to change. As it is known, in the process until 1980, the Turkish Republic dealt with structural problems encountered by most developing counties. These mainly include insufficient accumulation of capital, non-compliance in socioeconomic structure, and recycling techniques. These problems were tried to be solved in the process from 1923 to 1980, led by the government. Practices of development policies were followed in this process, led by many public sectors. Turkey's economic choice along with the change experienced after 1980 was, mainly, the establishment of free market economy; but because of the lack of necessary infrastructure, the state guarantee was applied as an inevitable choice. The worldwide economic recession and inflationist pressures in 1970s, undoubtedly affected Turkey as well. The stability decisions of January 24, announced by the ruling government on January 24, 1980, when evaluated from this point of view, were the start of the chain of measures to overcome the bottleneck that was fallen through. These measures taken had a powerful effect on the economy of Turkey after 1980. The financial situation of markets before 1980 can be summarized as: - The interest rates of deposit accounts and bank loans were under control; the real interest rates of bank loans were mostly negative in the atmosphere of high and volatile inflation. - Important restrictions were imposed on the foreign exchange transactions of banks and depositors (foreign exchange restrictions). - Persons could not have foreign currencies in their portfolios. - Subvention was provided to many sectors by means of preferred credit. Preferred credits constituted an important part in the formation of Central Bank's currency policy. - Sectors with priority in development were provided with cheap loans. - Transactions carried out in financial markets and revenues earned therefrom were taxed relatively higher. The cost of brokerage was high. - There was no institutionalized financial system. - Important restrictions were imposed on the entry of foreign and domestic banks to the financial system. - Bank loans were the only financing resource of companies. Since there was no security market, companies could not sell stocks for financing. Formation of companies with multiple shareholders by means of share ownership was tried, but a great failure was encountered (employee companies). - Disposability and compulsory provision rates were relatively high. - TL market was very scarce. - Ownership of companies and banks were within each other. All the above-cited elements significantly decreased the effectiveness of the financial system. The Turkish financial system comprises the Central Bank, deposit banks, development and investment banks, social security institutions, insurance companies, credit cooperatives and other financial intermediary establishments whose main function is to give and obtain loans. Whereas the non-financial sector comprises subsections such as public administrations, public enterprises, private enterprises and dwellers. The Turkish financial sector can be examined in five main groups: 1. The Central Bank (currency authority institution) 2. Deposit Banks i) Public Banks ii) Private Commercial Banks iii) Foreign Banks 3. Financial Service Institutions i) Security Institutions ii) Bankers 4) Other Financial Institutions (without power to create money) i) Development and Investment Banks ii) Credit Cooperatives iii) Insurance Companies iv) Security Investment Funds v) Security Investment Companies 5) Semi-Financial Institutions (Social security institutions such as Social Insurance Institution, T.R. Pension Fund and Bağ-Kur Employer’s Retirement Fund) In the last decade, the existence of important financial renovations draw attention. While the new technologies increase the recording speeds of operations on one side, they create new financial tools and institutions on the other side. The existence of complex and developed capital markets is interpreted as a sign of a developed economy. Financial liberalization in the Turkish economy, undoubtedly, has also allowed the financial markets to become deeper and the crises to be ended quickly. The negative effect of international capital that entered Turkey along with financial liberalization can be seen as a drop in domestic savings. However, this has not prevented economic growth, rather, a growth based on domestic savings and domestic consumption was achieved. But it is favorable for the country that the international capital should finance investment rather than consumption. When we look at the causes of financial crises, they can also be said to result from the price movements. In the periods when financial crises occur, those who work in the financial sector, shareholders, and those who use credit, encounter significant losses. In this case, a necessity to make an alignment in markets by public intervention can arise. Instabilities in financial markets in all countries will, undoubtedly, have differences and not be the same. Mainly; the search for liberal, market-supporting, externally open development, commenced in 1980, marked the last twenty years of the economy. The model of 1980, which represents a radical change, has completely changed the conventional understanding of development. Although the 1980s have been presented as a period in which liberalism was approved in full sense, it was actually a period in which public sector sustained its economic power, and public deficits and consequently inflationist pressures gained power in return. In principle, direct governmental interventions for allocation of resources were reduced and the achievement of an externally open industrialization was endeavored, led by the private sector. In an atmosphere where world trade and finance internationalize and markets globalize in higher and higher levels, achievement of Turkey's political and economic stability will make Turkey an important part of civilized world. Everybody has a duty here. During the latest periods, instability has existed widely not only in financial markets but generally in all the fields of economy. In such circumstances, instability played part in the determination of people's expectations from the future. In this case, the science of economics and the economists took the most important place. But the forecasts and solution offers caused mistakes from time to time. Here, the insufficiency of data obtained in the developing countries is important. Economy is made up of quite a complex structure, and its operation mechanism has not been yet uncovered completely. Here the main operating factors are the ones such as the short term capital movements of the economy, political problems, and natural disasters. These factors cannot be forecast and they impair the operation of the economy. Economists, however, make forecasts based on data of the past, and forecast the future in the light of these data. In Turkey, however, the optimism and pessimism of people about the general economy and the future of the country vary from day to day. Mass Communication Mediums (the Media) play an important part in these changes. This condition causes wrong forecasts to be made because of the insufficiency of data. This situation misleads both the society and the scientists, resulting in undesired consequences. The rise of general education level across the country and the consideration of science as a base, will contribute positively to the establishment and maintenance of stability. The real wealth of a nation is the people of that nation. Economic development is to achieve the goals which will facilitate realization of the creative and healthy long term expectations of people. Social development, whereas, is an important tool in achieving a better quality of life, decreasing poverty, increasing materialistic welfare, and eliminating the differences between regions and groups. The inactivation process of social development expenditures is global-orientated. Globalization phenomena has developed by the influence of developed countries on developing countries. In this developing process, the public weight has been intended to be decreased in the economic and social development of the public sector. In this context, the social development of developing companies does not conform to the social welfare approaches of developed countries. The approach of eroding the welfare state, which occurs in developed countries, may be a right approach for a global growth; however, cutting down the social development expenditures of developing countries, which do not even exist, results in the cession of individual and social protection mechanisms. The analysis of Turkey’s social development expenditures gave a result in this sense. Initiatives of eroding the non-existing social development expenditures of the public sector, constitute the core of the Turkish social crisis. In this context, the resulting public service deficit is the greatest obstacle in front of the individual and social development. Therefore, the recent arguments towards the shrinkage of public sector are the products of a search for a public sector which will inactivate the social development activated by the globalization process. As a result of global factors, the effectiveness of public economic and social institutions have disappeared. The public sector, however, is obliged to serve for a joint society ideal where individuals bearing social responsibilities as well as their individual rights cohabit in the market society, rather than individuals competing with each other insofar as possible. To conclude, Welfare, Justice, Peace, Understanding, Tolerance, Order, Knowledge, Morality and Quality are the principle global values for which mankind must fight for achieving. Turkey must recognize, learn, and endeavor to realize these new rising values as quickly as possible. Turkey, which does not attach importance to freedom, tolerance, understanding, morality, knowledge, quality of humans and systems, order, etc. , pays for this very hard. As Montaigne, the famous French philosopher said, “Things that cost us a lot are the most important values for us”. Turkey must assimilate the above mentioned elements consciously, and act so as not to expose its economy to greater crises. In an atmosphere where trade and finance move to an international integration, the achievement of political and economic stability in our country will help us to become an important part of the world.
Keywords: Banka ve bankacılık; BANKACILIK-SERMAYE; Ekonomi; FİNANS; Finansman ekonomisi